Richard Nixon’s Road towards America’s most Significant Crisis The Watergate Scandal - Boulahlib, Assia (Journal of Human Sciences, 2023)
This article provides a comprehensive portrait of one of the most complex and controversial figures in modern American history. It begins with Richard Nixon’s life and political career in California politics before delving into his controversial presidency along with the events leading up to the Watergate crisis. It traces the infamous break-in at the Democratic National Committee Headquarters and subsequent cover-up attempts. The article argues that Nixon’s road to the Watergate crisis was paved by his belief in the presidency’s inherent power and his willingness to use any means necessary to retain it. Ultimately, the Watergate scandal led to Nixon’s resignation and marked a turning point in American political history. It examines Nixon’s legacy and the ways in which his presidency continues to shape American politics and culture.